Staining Effect of Methanolic Extract of Hibiscus Sabdariffa Calyx on Thin Peripheral Blood Smear - Etim, Emmanuel Asuquo; Chagwa, Ezekiel Friyanda; Obeagu, Emmanuel Ifeanyi; Udokang, Akpan Akaninyene (Journal of Diseases, 2019)
Hibiscus sabdariffa is a species of Hibiscus in the Malvaceae family. Hibiscus sabdariffa is widely consumed as Zobo drink beverage in Nigeria with many health benefits, and it is believed that the brilliant reddish coloration of methanolic extract of this plant’s calyx may have a staining effect on thin blood smear. Hence, this study aims to examine the staining effect of methanolic extract of Hibiscus sabdariffa calyx on thin peripheral blood films in other to obtain more surrogates for hematological stains. Dried calyx of Hibiscus sabdariffa was obtained commercially from Yola. The calyces were pulverized to fine powder and 10g of the powder was soaked in 50ml of absolute methanol for 12hours to obtain methanolic extract. PH of the extract was determined using PH meter. The methanolic extract was used to stain thin peripheral blood smear. Results: Raw methanolic extract of Hibiscus sabdariffa calyx had pH of 1. The extract produces poor staining effect and impacted a pale pinkish-orange appearance on the red blood cells with pseudo large central pallor microscopically. While field stain and Leishman stain produces a dark pink coloration with normal pallor on the red cell. Raw methanolic extract of Hibiscus sabdariffa calyx was acidic and it impacted a poor pale pinkish-orange coloration with pseudo large pallor on red blood cell in thin peripheral blood smear. More research to get a molar equilibrium of acidic and basic substances in this plant’s calyx extract is recommended in other to obtain more cost effective surrogates for good hematological stains.